Entrepreneurship Competency Model Through Supply Chain Integra-tion on Competitive Advantage in Small Businesses in The Food and Beverage Sector in North Bandung Area - Asep Kurniawan; Yun Yun (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
Competitive advantage becomes capital for a business to continue to grow and develop. One of them is in the culinary field, where the culinary business in the North Bandung area is currently growing. This has an impact on the need for increasing competence of small business actors to be able to implement supply chain integration that is able to gain a competitive advantage. Entrepreneurial competence and supply chain integration can be used as capital for small business actors to gain competitive advantage for small business actors in the culinary field in the North Bandung area. This study aims to determine the model of entrepreneurial competence through supply chain integration to competitive advantage. The model used is partial least square- Structural Equation Modeling (SEM). The population and sample in this study are small business actors in the culinary field in the North Bandung area. Entrepreneurship competence has a significant influence on competitive advantage through supply chain integration. This shows that to increase the competitive advantage of the food and beverage business in West Bandung Regency, it can be done through supply chain integration and paying attention to the entrepreneurial competence of food and beverage business actors in West Bandung Regency.